Influence of increasing differential settlement under columns on a RC frame response considering different support conditions - Alireza Pachenari (Iranian Society of Structrual Engineering (ISSE), 2019)
Natural hazards and human activities bring about overall or local ground subsidence. Predicting the effects of large differential settlement on response of structural frames, especially in congested urban areas, is a main issue in design process as inadvertence can lead to irrecoverable human and financial losses. In order to better understand the consequences of the subsidence phenomenon on the superstructure, a three dimensional reinforced concrete (RC) moment frame designed according to the current Iranian codes of practice is analyzed due to six separate nonlinear analysis cases considering three locations for the increasing differential settlements (under corner, exterior, and interior columns) as well as two support conditions (fixed and flexible); Various results including change in pattern of bridging beam bending moments, axial force redistribution in columns, and also maximum tolerable elastic and inelastic settlements are evaluated. Based on the findings of the numerical models, although cases with the settlement imposed under an interior column have the least vertical downward displacement at formation of first plastic hinge in a beam compared to corresponding cases, the highest capacity to bear differential settlement occurs due to one of the cases of a corner column location. Moreover, formation of plastic hinges and redistribution of axial forces in first-story columns are highly affected by the modeled support conditions.